The Role of microRNAs in the Drosophila Melanogaster Visual System - Colaianni, Davide; De Pittà, Cristiano (Frontiers in Cell and Developmental Biology, 2022)
MicroRNAs (miRNAs) are a class of small non-coding RNAs (~22 nucleotides in length) that negatively regulate protein-coding gene expression post-transcriptionally by targeting mRNAs and triggering either translational repression or RNA degradation. MiRNA genes represent approximately 1% of the genome of different species and it has been estimated that every miRNA can interact with an average of 200 mRNA transcripts, with peaks of 1500 mRNA targets per miRNA molecule. As a result, miRNAs potentially play a fundamental role in several biological processes including development, metabolism, proliferation, and apoptotic cell death, both in physiological and pathological conditions. Since miRNAs were discovered, Drosophila melanogaster has been used as a model organism to shed light on their functions and their molecular mechanisms in the regulation of many biological and behavioral processes. In this review we focus on the roles of miRNAs in the fruit fly brain, at the level of the visual system that is composed by the compound eyes, each containing ~800 independent unit eyes called ommatidia, and each ommatidium is composed of eight photoreceptor neurons that project into the optic lobes. We describe the roles of a set of miRNAs in the development and in the proper function of the optic lobes (bantam, miR-7, miR-8, miR-210) and of the compound eyes (bantam, miR-7, miR-9a, miR-210, miR-263a/b, miR-279/996), summarizing also the pleiotropic effects that some miRNAs exert on circadian behavior.